A Reactive Element Approach to Improve Fracture Healing in Metallic Systems - Fisher, Charles R.; Jr., John J. Mecholsky; Henderson, Hunter B.; Kesler, Michael S.; Manuel, Michele V. (Frontiers in Materials, 2019)
Self-healing materials demonstrate the ability to close fractures and regain mechanical integrity after a catastrophic failure. However, self-healing in metals can be inhibited by the natural tendency for technologically-relevant metallic systems to oxidize on the crack surface. This study seeks to provide a thermodynamically-based mechanism to enhance healing capability at a solid/liquid interface through alloys designed with a reactive element alloying addition possessing a lower free energy of oxide formation than the parent element. In this study, model Sb-Cu and Sb-Zn systems enable comparisons between mechanistic behaviors based only on thermodynamic reactivity. Mechanical and microstructural investigation demonstrated that the more reactive alloying addition resulted in more effective bonding through increasing bond area and load-bearing capacity of the system. The improved bonding was attributed to improved wetting and reduction of the passivating surface oxide across an interface. The work has potential to advance self-healing capabilities in metallic systems through more appropriate alloy selection to enable improved healing.